A stochastic programming approach for wildfire suppression : prepositioning and distribution of resources under uncertainty (2017)
"Wildfires suppression is a problem of big interest in literature because of the threat that these events represent to communities, the buildings and the environment. To control these events, firemen realize tactic operations to stop the wildfire propagation using techniques such as firelines, water attacks and retardant chemicals. The success of the attack depends on the resources available and the time of arrival of these resources to the attack zone, making the resource location essential to control the wildfire. A mixed integer stochastic optimization model is proposed to represent the scenarios of wildfires, using a time-expanded graph to represent the dynamics of propagation. The model seeks to minimize the expected costs, including: facilities cost, resource location costs, and expected cost of distribution, excess and shortage of inventory..."-- Tomado del Formato de Documento de Grado.